Chapter Introduction Why Refugee Self-Reliance? - Easton-Calabria, Evan (Bristol University Press, 2022)
The first chapter is available Open Access under CC-BY-NC-ND license. Evan Easton-Calabria's critical history of refugee self-reliance assistance brings new dimensions to refugee and international development studies. The promotion of refugee self-reliance is evident today, yet its history remains largely unexplored, with good practices and longstanding issues often missed. Through archival and contemporary evidence, this book documents a century of little-known efforts to foster refugee self-reliance, including the economic, political, and social motives driving this assistance. With five case studies from Greece, Tanzania, Pakistan, Uganda, and Egypt, the book tracks refugee self-reliance as a malleable concept used to pursue ulterior interests. It reshapes understandings of refugee self-reliance and delivers important messages for contemporary policy making.